Women’s Participation in the Labor Market and Children’s Educational Progress in Senegal - Mamadou Laye Ndoye; Touwédé Bénédicte Atchade (Economies)
This research aimed to better understand the impact of a mother’s work on girls’ and boys’ school progression at the end of primary school in Senegal. The observed correlations between a child’s educational success and the mother’s labor market involvement may not indicate causation but could instead result from other shared factors influencing both variables (an endogeneity issue). To address this issue, we estimated a bivariate model with two equations, one explaining the mother’s participation in the labor market and the other explaining the child’s educational survival, applied to data from the Integrated Regional Survey on Employment and the Informal Sector (ERI-ESI-2018). We discovered that certain individual characteristics, such as age, education level, and marital status, as well as family characteristics, including household size and parents’ social background, play significant roles in maintaining women’s labor market activity. Furthermore, we concluded that mothers’ participation in the labor market has a positive and significant effect (at 10%) on boys’ success in primary school exit exams, while the impact on girls is negative and not statistically significant. When controlling for various factors, we found that children whose mothers possess higher levels of education are more likely to pass their primary school exams. The results highlight the significance of women’s education, underscoring its role in not only integrating women into the labor market, but also in fostering their children’s academic success. In terms of economic policy implications, the study suggests that state authorities should continue to invest more in improving women’s literacy rates and in strengthening their academic and professional capacities, thereby enabling them to achieve advanced levels of education and higher qualifications.